Immune damage mechanisms of COVID-19 and novel strategies in prevention and control of epidemic - Sun, Yuting; Luo, Bin; Liu, Yueping; Wu, Yuzhang; Chen, Yongwen (Frontiers in Immunology, 2023)
Caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), coronavirus disease 2019 (COVID-19) has diverse clinical manifestations, which is the main feature of the disease, and the fundamental reason is the different immune responses in different bodies among the population. The damage mechanisms of critical illness by SARS-CoV-2 and its variants, such as hyperinflammatory response, a double-edged function of type I interferon, and hyperactivation of the complement system, are the same as other critical illnesses. Targeting specific immune damage mechanisms of COVID-19, we scored the first to put forward that the responses of T cells induced by acute virus infection result in “acute T-cell exhaustion” in elderly patients, which is not only the peripheral exhaustion with quantity reduction and dysfunction of T cells but also the central exhaustion that central immune organs lost immune homeostasis over peripheral immune organs, whereas the increased thymic output could alleviate the severity and reduce the mortality of the disease with the help of medication. We discovered that immune responses raised by SARS-CoV-2 could also attack secondary lymphoid organs, such as the spleen, lymphoid nodes, and kidneys, in addition to the lung, which we generally recognize. Integrated with the knowledge of mechanisms of immune protection, we developed a coronavirus antigen diagnostic kit and therapeutic monoclonal antibody. In the future, we will further investigate the mechanisms of immune damage and protection raised by coronavirus infection to provide more scientific strategies for developing new vaccines and immunotherapies.